5x-9-2x=7

Simple and best practice solution for 5x-9-2x=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-9-2x=7 equation:


Simplifying
5x + -9 + -2x = 7

Reorder the terms:
-9 + 5x + -2x = 7

Combine like terms: 5x + -2x = 3x
-9 + 3x = 7

Solving
-9 + 3x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 3x = 7 + 9

Combine like terms: -9 + 9 = 0
0 + 3x = 7 + 9
3x = 7 + 9

Combine like terms: 7 + 9 = 16
3x = 16

Divide each side by '3'.
x = 5.333333333

Simplifying
x = 5.333333333

See similar equations:

| -9(x+19)=7+6 | | -16=-4+3n | | 2x/5+11/2=8 | | 4(5x-4)=4x+12 | | 4(5x-4)=4x+13 | | (1+x)2-5+4x=3 | | 64+d=138 | | -3x-2(3x+7)=58 | | 360-.75x^2=0 | | 2y+17=45 | | 36=6p | | 8h=10h | | 5(3-w)=50 | | -3-2(3x+7)=58 | | Y+8x=-3 | | -.33(3y+5)= | | 4a+5=3a-1 | | 9x+4x+32=72 | | x^2+2x+121=0 | | -6x-3(-6x-17)=-69 | | Xy+y-2x-3=0 | | 8s+5s+2s-5= | | 18x-3(6x-1)=8 | | 80=5y-15 | | -11+10(x+10)=5+4(2x+11) | | 24=20+x | | 5d+6=8d-69 | | -9+(4x-2)=-(5z+5)+1 | | Y-9=x+6 | | p+27=41 | | 30+5.50A=8 | | -3f+4=-14 |

Equations solver categories